mCherry fusions enable the subcellular localization of periplasmic and cytoplasmic proteins in Xanthomonas sp. - Pena, Michelle Mendonça [UNESP]; Teper, Doron; Ferreira, Henrique [UNESP]; Wang, Nian; Sato, Kenny Umino [UNESP]; Ferro, Maria Inês Tiraboschi [UNESP]; Ferro, Jesus Aparecido [UNESP] (Public Library of Science (PLoS), 2020)
Fluorescent markers are a powerful tool and have been widely applied in biology for different purposes. The genome sequence of Xanthomonas citri subsp. citri (X. citri) revealed that approximately 30% of the genes encoded hypothetical proteins, some of which could play an important role in the success of plant-pathogen interaction and disease triggering. Therefore, revealing their functions is an important strategy to understand the bacterium pathways and mechanisms involved in plant-host interaction. The elucidation of protein function is not a trivial task, but the identification of the subcellular localization of a protein is key to understanding its function. We have constructed an integrative vector, pMAJIIc, under the control of the arabinose promoter, which allows the inducible expression of red fluorescent protein (mCherry) fusions in X. citri, suitable for subcellular localization of target proteins. Fluorescence microscopy was used to track the localization of VrpA protein, which was visualized surrounding the bacterial outer membrane, and the GyrB protein, which showed a diffused cytoplasmic localization, sometimes with dots accumulated near the cellular poles. The integration of the vector into the amy locus of X. citri did not affect bacterial virulence. The vector could be stably maintained in X. citri, and the disruption of the α-amylase gene provided an ease screening method for the selection of the transformant colonies. The results demonstrate that the mCherry-containing vector here described is a powerful tool for bacterial protein localization in cytoplasmic and periplasmic environments.